Aplicación móvil multiplataforma que brinda información de las unidades de salud públicas y privadas de la ciudad de Loja. - Atiencia Pogo, Kevin Luis (2017)
Today the medias of outreach that use public and private health units are not competent, or the most appropriate to provide information about the specialties and services, which they offer to the society of the city of Loja. Is why this final work degree is based on the analysis and development of two applications: a mobile called HUY (Health Units Information), that it can be used in different operating systems, allowing you to locate health units through GPS, also allows search specialties and get complete information of services , opening hours , telephone numbers, addresses, level attention, among other aspects. In addition, built a web application addressed to the Manager, dedicated to manage and administer the information of health units, specialties and services. This aplication is called HUIS (Health Units Information System). For the development of the software, the methodology was used Agile Extreme Programming (XP), due to the fact that adapts to the needs of the project, is flexible to changing requirements vague and requires a limited working group and its development process is easy to use. Also the use of the deductive methods, allows an orderly process of the development of work of qualification. Starting from the application of techniques such as the bibliographic, which helps obtain the most relevant information of the tools and technologies needed for the construction of applications and the use of surveys, used for the collection of information on the needs and requirements present in a sample size of the city of Loja. To reach specific, resulting in the obtaining of the pone and web application functional and free of errors that could harm their performance.